PUBLIC SERVICES AT THE SALANG DISTRICT OFFICE, SIMEULUE REGENCY - Cut Lasmi; Ahmad Yani; Risna Dewi; Ti Aisyah; Syamsuddin (RADJA PUBLIKA, 2025)
This study aims to determine how public services are implemented at the Salang District Office, Simeulue Regency, and to identify factors that influence the quality of these services. The background of this study is based on the phenomenon of public services that are not fully optimal, where various obstacles are still found, such as limited human resources, inadequate facilities and infrastructure, and the ability of the apparatus to operate information technology that is still limited. This study uses the theory of public service quality with reference to three main dimensions, namely reliability which includes consistency, accuracy, and trustworthiness. Then, responsiveness which includes speed, accuracy, and precision. And empathy which includes caring, responsiveness, and sensitivity. The method used in this study is a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The data obtained are then analyzed through the stages of data reduction, data presentation, and data verification. The results of the study indicate that public services at the Salang District Office, Simeulue Regency, generally run well. From the aspect of reliability, employees are able to provide services quickly, accurately, and in accordance with applicable procedures. In terms of responsiveness, employees demonstrated agility in responding to public needs and complaints with good communication and polite behavior. Meanwhile, in terms of empathy, employees were assessed as friendly, patient, and concerned about the community's situation, creating a comfortable service atmosphere. Overall, public services at the Salang Sub-district Office have been running quite effectively and have earned the trust of the public. Although increasing employee capacity and equalizing service quality are still needed to optimize public services in the future.